The level of Arabic language teachers’ ability to develop skills Critical speaking among high school students - Abdelkader, Mahmoud Helal (Journal of Educational and Psychological Sciences, 2023)
The aim of the current research is to reveal the level of Arabic language teachers’ ability to develop critical speaking skills for secondary school students; To achieve this goal, research materials and tools were prepared, which consisted of: a list of critical speaking skills appropriate for students of secondary school students, a list of methods for developing critical speaking skills for students of secondary school students, a note card for methods of developing critical speaking skills, and then ensuring the stability and validity of Those tools, then selecting the research sample from the Arabic language teachers in Asir education, then applying the study tool to the research sample, then statistical analysis and interpretation of the results and making recommendations and suggestions. And there were no differences due to years of service or training courses in the ability of Arabic language teachers to develop critical speaking skills among high school students.